A Coordinating Strategy for Biofuel Supply Chain under Disturbance Using Revenue Sharing Contract Approach - Geng, Nana; Zhang, Yong; Sun, Yixiang (Promet - Traffic&Transportation, 2018)
Biofuel is considered to be an important alternative energy in the future transportation. Its development is supported by the rest of the world. However, biofuel industry development is still very slow. From the previous research it is known that the supply chain coordination and other problems need to be solved to promote the supply chain ability. This paper studies biodiesel supply chain coordination problem from the view of disturbance management. It gives a disturbed coordination strategy which contains the optimal order quantity and the contract parameters. This paper has then verified the disturbed coordination strategy through using the actual data of Jiangsu Yueda Kate New Energy Co. Ltd. The result shows that when the market demand and the recovery cost are simultaneously disturbed, the coordination can make the biodiesel supply chain robust and the new strategy under the revenue sharing contract is better than the original one.